The Effect of Whatsapp Video-Based Education on Delivery on Knowledge and Attitude of Pregnant Women in Trimester III in The Time of Covid-19 - Husna Husna; Ningsih Saputri; Embun Nadya (Institute of Computer Science (IOCS), 2022)
Childbirth is the process of expelling the products of conception (fetus and uri) that are already months old or can live outside the womb through the birth canal, with or without assistance. In Indonesia, the utilization of the coverage of ANC visits is still less than the expected target during this covid 19 period. one of them is in the Working Area of the Gunung Medan Health Center, Dharmasraya Regency in 2021 the K1 visit rate only reached 52% and K4 44%. Research. This study aims to determine the effect of WhatsApp Video-Based Counseling on Childbirth on the Knowledge and Attitudes of Third Trimester Pregnant Women during the Covid-19 period in the Gunung Medan Public Health Center, Dharmasraya Regency. This study uses a True Experimental Design that is used in this study is Posttest-Only Control Design. The population in this study were all third trimester pregnant women living in the Gunung Medan Public Health Center, Dharmasraya Regency with a sample of 40 people. Analysis of this data using the T Test Independent with a significance value of 0.001 <0.05. There is an effect of WhatsApp Video-Based Counseling on Childbirth on the Knowledge and Attitudes of Third Trimester Pregnant Women during the Covid-19 period in the Gunung Medan Health Center Working Area, Dharmasraya Regency.